Characterization of Novel Erwinia amylovora Jumbo Bacteriophages from Eneladusvirus Genus - Sang Guen Kim; Sung Bin Lee; Sib Sankar Giri; Hyoun Joong Kim; Sang Wha Kim; Jun Kwon; Jungkum Park; Eunjung Roh; Se Chang Park (Viruses, 2020)
Jumbo phages, which have a genome size of more than 200 kb, have recently been reported for the first time. However, limited information is available regarding their characteristics because few jumbo phages have been isolated. Therefore, in this study, we aimed to isolate and characterize other jumbo phages. We performed comparative genomic analysis of three Erwinia phages (pEa_SNUABM_12, pEa_SNUABM_47, and pEa_SNUABM_50), each of which had a genome size of approximately 360 kb (32.5% GC content). These phages were predicted to harbor 546, 540, and 540 open reading frames with 32, 34, and 35 tRNAs, respectively. Almost all of the genes in these phages could not be functionally annotated but showed high sequence similarity with genes encoded in Serratia phage BF, a member of Eneladusvirus. The detailed comparative and phylogenetic analyses presented in this study contribute to our understanding of the diversity and evolution of Erwinia phage and the genus Eneladusvirus.